Object‐Oriented Identification of Coherent Structures in Large Eddy Simulations: Importance of Downdrafts in Stratocumulus. Issue 5 (4th March 2019) - Brient, Florent; Couvreux, Fleur; Villefranque, Najda; Rio, Catherine; Honnert, Rachel
Abstract: A novel methodology is proposed to characterize coherent structures in large eddy simulations. Based on two passive tracers emitted respectively at the surface and at cloud top, the object‐oriented framework allows individual characterization of coherent tridimensional plumes within the flow. Applying this method in a simulation of the diurnal cycle of a marine stratocumulus‐topped boundary layer shows that coherent updraft and downdraft structures contribute to most of the total transport of heat and moisture, although covering a small part of the domain volume. On average, downdrafts contribute equally compared to updrafts for moisture fluxes and more than updrafts for heat fluxes. The relative contribution of updraft and downdraft objects to heat transport exhibits a large diurnal cycle, which suggests cloud‐turbulence‐radiation interaction. Our results suggest that subgrid downdraft properties within stratocumulus‐topped boundary layers should be represented through nonlocal mass‐flux parameterization in climate models. Plain Language Summary: The representation of marine stratocumulus remains significantly biased in climate models, which lead to important uncertainties in the simulation of the present‐day climate and in projections of future climate change. These errors are related to the way boundary‐layer clouds are represented through empirically defined parameterizations. To improve cloud representation, we need better understanding of boundary layer processes. Here we use a novel methodology that use passive tracers to define as objects individual coherent structures. One advantage of this framework is that it does not have a priori assumption of flow characteristics for defining them. Although occupying a small part of the volume, those structures carry most of heat and moisture within a diurnal cycle of a stratocumulus‐topped boundary layer. We found that downdrafts plumes contribute as much as updrafts to these transports. Contrary to what is used in most of boundary layer parameterizations, the object‐oriented analysis suggests that nonlocal mass‐flux assumptions are more appropriate for representing downdrafts in climate models. Key Points: Boundary‐layer coherent structures are identified as objects in a stratocumulus large eddy simulation Both downdrafts and updrafts contribute significantly to heat and moisture transport, although covering only a small fraction of the domain A mass‐flux parameterization is appropriate for representing downward transport within stratocumulus‐topped boundary layer in climate models